PENGARUH KOMUNIKASI KELOMPOK TERHADAP DINAMIKA KELOMPOK TANI PADI SAWAH DI DESA LABULU-BULU KECAMTAN PARIGI KABUPATEN MUNA - Helsa Patiumala; Ima Astuty Wunawarsih; Megafirmawanti Lasinta (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The present farmer organizations merely serve as instruments through which select communities or specific groups may procure assistance from the government. Consequently, the establishment of farmer groups has deviated from its initial objective, which was to enhance the well-being of the farming community through agricultural development. The objective of this study is to ascertain the impact of group communication on the dynamics of paddy rice farmer groups in Labulu-bulu Village, Parigi District, Muna Regency. The study population comprised 324 wet-rice farmers. The sample size was determined using the Slovin formula with a margin of error of 15%, resulting in a sample of 39 respondents for this study. The sampling method employed was the Proportional Stratified Random Sampling technique. The data were collected using survey and interview methods guided by questionnaires. The independent variables of this study include group communication (X) and farmer group dynamics (Y). The collected data is then subjected to a descriptive and quantitative analysis. A descriptive analysis was conducted using the interval formula, and a linear regression analysis was performed with the assistance of SPSS software version 16. The findings indicated that the communication patterns exhibited by paddy rice farmer groups in Labulu-Bulu Village were classified as high-intensity, characterized by a strong sense of solidarity, frequent interactions, and a high level of motivation. The dynamics of paddy rice farmer groups are in the high or dynamic category based on group objectives, group structure, task function, and group effectiveness. The findings of this study demonstrate that group communication exerts a substantial influence (p < 0.05) on the dynamics of rice paddy farmer groups. Accordingly, it can be concluded that group communication on indicators of solidarity, communication intensity, communicative action, and communication motivation will affect group dynamics. The aforementioned group dynamics include indicators of group objectives, group structure, task function, and group effectiveness.